2020
DOI: 10.3390/ijgi9100562
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Soil Erosion Rate Changes in Areas Affected by Wildfires

Abstract: In recent decades, wildfires have become a serious threat worldwide, producing disasters in the natural and anthropogenic environment as well as serious economic losses. One of wildfire’s major impacts is soil erosion, as it may cause major problems in both the physical and anthropogenic environment and seriously affect the landscape. This study investigates the soil erosion rate changes in areas affected by wildfires and uses, as a pilot area, the drainage basin of the Pinios earth-filled dam located in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The Northern burned zone is mainly characterized by agricultural, hilly areas of smooth relief and altitudes up to 800 m, while the Southern has more mountainous and forest terrain, with altitudes up to 1335 m and steeper slopes. The rate of increase in the soil erosion rate on the Northern part of the study area immediately after the wildfire event was found to be equal to 36.2%, with the percentage reducing to 31% after a decade [62]. This is an important circumstance for the study area since soil erosion accelerates landslide occurrence, especially when rainfall infiltrates eroded areas.…”
Section: Study Areamentioning
confidence: 89%
“…The Northern burned zone is mainly characterized by agricultural, hilly areas of smooth relief and altitudes up to 800 m, while the Southern has more mountainous and forest terrain, with altitudes up to 1335 m and steeper slopes. The rate of increase in the soil erosion rate on the Northern part of the study area immediately after the wildfire event was found to be equal to 36.2%, with the percentage reducing to 31% after a decade [62]. This is an important circumstance for the study area since soil erosion accelerates landslide occurrence, especially when rainfall infiltrates eroded areas.…”
Section: Study Areamentioning
confidence: 89%
“…In other countries, such as the Mediterranean ones, despite an increasing number of hazardous events (Parise and Cannon 2008;Tiranti et al 2006;Carabella et al 2019;Esposito et al 2013Esposito et al , 2017Esposito et al , 2019, no model for the hydro-geomorphic events susceptibility assessment has been implemented or validated extensively. Very few examples of model application can be found in Italy, Greece, Portugal and Spain (Terranova et al 2009;Fernandez et al 2010Fernandez et al , 2018Coschignano et al 2019;Esteves et al 2013Rulli et al 2013Lanorte et al 2019;Depountis 2020, Efthimiou 2020. The need to quantify the influence of fires on the propensity for hazardous processes clashes with the fact that, in many regions outside the United States, the scientific community has faced the problem in a consistent way only in recent years and thus the available post-fire event statistics does not allow for a data driven approach.…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion rates in the Mediterranean region are expected to accelerate because of the frequent appearance of intense rainfall episodes, which contribute to the intensification of the erosion process and, therefore, the watersheds' degradation [3,4]. Significant environmental consequences of soil erosion include water quality deterioration, soil degradation, floods and land disasters [5], as well as increased sediment generation, transportation and deposition in natural lakes and water reservoirs [6][7][8]. In the natural environment, the balance of soil loss is achieved by soil regeneration through rock weathering and pedogenesis.…”
Section: Introductionmentioning
confidence: 99%